An experimental and theoretical approach to the 2-chloro-1-(3-methyl-3-phenylcyclobutyl) ethanone - Dincer, Muharrem; Ozdemir, Namik; Yilmaz, Ibrahim (Int Union Crystallography, 2008)
[Abstract Not Available]
Keywords: crystallographic analysis; organic crystals; theoretical calculations